Anti-β2-glycoprotein I antibodies are associated with pregnancy loss in women with the lupus anticoagulant - Sailer, Thomas; Zoghlami, Claudia; Kurz, Christine; Rumpold, Helmut; Quehenberger, Peter; Panzer, Simon; Pabinger, Ingrid (Thrombosis and Haemostasis, 2006)
The presence of lupus anticoagulant (LA) predisposes to fetal loss and to venous and arterial thrombosis; however, a subgroup of women is unaffected by pregnancy loss. Currently, no predictive markers are available for the identification of women positive for LA at increased risk for pregnancy loss. It was the aim of our study to investigate whether increased anti-β2-GPI-antibodies predict pregnancy loss in women positive for LA. We performed a cross-sectional study in a cohort of 39 women with persistent LA, who had in total 111 pregnancies. Fifteen women had exclusively normal pregnancies (30 pregnancies) and 24 women had pregnancy losses (81 pregnancies). Anti-β2-GPI-antibodies were determined using a semiquantitative enzyme linked immunoassay (QUANTA Lite™ β2 GPI IgG and IgM; Inova Diagnostics). Increased levels of anti-β2-GPI antibodies were significantly associated with pregnancy loss [odds ratio (OR) 9.6, 95% confidence interval (CI) 1.6 – 56.4].This risk was even higher in the subgroup of women (n=16) with more than two miscarriages or fetal loss after the first trimester [OR 13.1, 95% CI 1.4 – 126.3]. There was no significant association between anticardiolipin antibodies and pregnancy loss [OR 3.5, 95% CI 0.7 – 17.6].The coexistence of anti-β2-GPI and anticardiolipin antibodies was also predictive for pregnancy loss [OR 6.1, 95%CI 1.3 – 29.7]. Interestingly, the prevalence of thrombosis was similar between women with normal pregnancy (87%) and those with pregnancy loss (75%). We conclude that increased levels of anti-β2-GPI antibodies are predictive for pregnancy loss among women positive for LA, and that prophylactic treatment should be considered in these women even without a history of previous pregnancy loss.
Keywords: Lupus anticoagulant; pregnancy loss; anti-β2-glycoproteinI antibodies; anticardiolipin antibodies; antiphospholipid syndrome